Introduction to the front office & reception - 4 0 16; 5 Video Education Australasia (Victoria, Australia : VEA)
This program considers the roles and responsibilities of the duty manager, concierge and porter at a five star hotel contrasts these with duties of the manager of a youth hostel and the general manager of a three and ahalf star motor inn.
DVD format.
Keywords: 2 -- 0; 6; Employees. -- Hotel front desk personnel.;Hotel;Hospitality industry. -- 20; 20; 2